Perancangan Radiofarmaka Teranostik Kanker Penargetan Transporter Asam Amino Tipe-L1: Simulasi Docking Molekuler - Abdul Holik, Holis; Achmad, Arifudin; Maulana Ibrahim, Faisal; Alysia Elaine, Angela; Stefanus, Jonathan; Sudarmanto, B.S. Ari Sudarmanto; S. Kartamihardja, Achmad Hussein (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Abstract. L-type amino acid transporter 1 (LAT1) is a potential pan-cancer theranostic molecular target. The LAT1 inhibitory potencies of eight theranostic radiopharmaceuticals designed based on a potent LAT1 inhibitor ADPB (in vitro pIC50 6.19), were estimated in molecular docking simulations. The designs comprised ADPB as a carrier molecule with/without 6-aminohexanoic acid (Ahx) linker, a chelating agent, and a radiometal (68Ga or 177Lu). JPH203, the most potent LAT1 inhibitor (pIC50 7.22), was utilized as a benchmark compound. A set of known LAT1 ligands (n = 15) were first docked into LAT1 to build the docking protocol. Adding a linker improved the LAT1 inhibitory potency of DOTA-conjugated and NODAGA-conjugated ADPB-based theranostic radiopharmaceutical designs. 177Lu-DOTA-Ahx-ADPB has the exceptional LAT1 inhibitory potency (pIC50 51.55 ± 17.06) while 177Lu-DOTA-ADPB, its non-linker counterpart, has LAT1 inhibitory potency significantly higher than the native JPH203. Both 177Lu-DOTA-Ahx-ADPB and 177Lu-DOTA-ADPB have strong bonds with key amino acids on the LAT1 binding pocket, particularly Asn258, Tyr259, and the gating residue Phe252. Our findings provide a quantitative and illustrative understanding of the LAT1 inhibitory potency of LAT1-targeting theranostic radiopharmaceutical designs relevant to the rational design of pan-cancer radiotheranostic drugs. Keywords: LAT1, pan-cancer, theranostic radiopharmaceutical, MOE, chelating agent, gallium-68, lutetium-177.